NGSS Scientific Practices in an Elementary Science Methods Course: Preservice Teachers Doing Science - Morrison, Judith (Innovations in Science Teacher Education, 2021)
To engage elementary preservice teachers enrolled in a science methods course in authentically doing science, I developed an assignment focused on the NGSS scientific practices. Unless preservice teachers engage in some type of authentic science, they will never understand the scientific practices and will be ill-equipped to communicate these practices to their future students or engage future students in authentic science. The two main objectives for this assignment were for the PSTs to gain a more realistic understanding of how science is done and gain confidence in conducting investigations incorporating the scientific practices to implement in their future classrooms. To obtain evidence about how these objectives were met, I posed the following questions: What do PSTs learn about using the practices of science from this experience, and what do they predict they will implement in their future teaching relevant to authentic investigations using the scientific practices? Quotes from preservice teachers demonstrating their (a) learning relevant to doing science, (b) their struggles doing this type of investigation, and (c) predictions of how they might incorporate the scientific practices in their future teaching are included. The assignment and the challenges encountered implementing this assignment in a science methods course are also described.